2018
DOI: 10.1111/plb.12703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exogenous double‐stranded RNA movement in in vitro peanut plants

Abstract: New technologies are needed to eliminate mycotoxins and/or fungal pathogens from agricultural products. RNA interference (RNAi) has shown potential to control fungi associated with crops. In RNAi, double-stranded RNA (dsRNA) targets homologous mRNA for cleavage, and can reach the mRNA of pathogens in contact with the plant. The key element in this process is the movement of RNA signals cell-to-cell and over long distances within the plant, and between host plants and parasites. In this study, we selected a reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Koch et al [13] reported on the fluorescent signal detection of labeled dsRNA in barley vascular tissue 24 h after spraying. Faustinelli et al [74] demonstrated that exogenously applied synthetic 27 nt siRNAs spread systemically and were stable for at least 30 days in in vitro peanut plants. In addition, there are several studies reporting on the stability of dsRNA applied onto plant leaf surfaces and showing that dried naked dsRNA or dsRNA loaded into LDH nanosheets were stable on plant surfaces for up to 30 days [10,19].…”
Section: Plant Nucleic Acid Recognition and Uptakementioning
confidence: 99%
“…Koch et al [13] reported on the fluorescent signal detection of labeled dsRNA in barley vascular tissue 24 h after spraying. Faustinelli et al [74] demonstrated that exogenously applied synthetic 27 nt siRNAs spread systemically and were stable for at least 30 days in in vitro peanut plants. In addition, there are several studies reporting on the stability of dsRNA applied onto plant leaf surfaces and showing that dried naked dsRNA or dsRNA loaded into LDH nanosheets were stable on plant surfaces for up to 30 days [10,19].…”
Section: Plant Nucleic Acid Recognition and Uptakementioning
confidence: 99%
“…Our results also show that siRNAs were generated from the introduced dsRNA insert, and that the majority of the siRNAs mapped to afl ep, followed by pes 1, while fewer mapped to afl R. Since the siRNAs that mapped the RNAi-5x insert showed high abundance on specific areas of the insert, both for dsRNA and for dsDNA treatments, the sRNAs were interpreted as being generated de novo; a uniform coverage would be expected if they had originated from dsRNA degradation. In our previous study, we had observed a quantitative increase in the amount of RNA duplexes over time 25 .…”
Section: Discussionmentioning
confidence: 87%
“…204243 (Qiagen, Germantown, MD, USA). The stemloop primers were designed as described previously 25 . Stemloop, forward and reverse primers, and synthetic sequences of the small RNAs that were validated (the DNA oligonucleotides), were obtained from Integrated DNA Technologies (IDT, Coralville, Iowa, USA) ( Table 2).…”
Section: Validation Of Srnas By Stemloop Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of leaves with artificially synthesized dsRNAs targeted at the genes involved in insect development significantly increases mortality and inhibits insect growth [88][89][90][91][92]. This effect can be achieved by irrigating the roots of plants by dsRNA, which leads to effective suppression of the target gene and abnormal development of insect pests [74,76,93]. RNA interference using exogenous dsRNAs can be used for a very wide range of insect genes.…”
Section: Methods For Delivery Of Artificial Double-stranded Rnas In Pmentioning
confidence: 99%